2017
DOI: 10.1002/cne.24245
|View full text |Cite
|
Sign up to set email alerts
|

Study of retinal neurodegeneration and maculopathy in diabetic Meriones shawi: A particular animal model with human‐like macula

Abstract: The purpose of this work was to evaluate a potentially useful animal model, Meriones shawi (M.sh)-developing metabolic X syndrome, diabetes and possessing a visual streak similar to human macula-in the study of diabetic retinopathy and diabetic macular edema (DME). Type 2 diabetes (T2D) was induced by high fat diet administration in M.sh. Body weights, blood glucose levels were monitored throughout the study. Diabetic retinal histopathology was evaluated 3 and 7 months after diabetes induction. Retinal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 85 publications
3
16
0
Order By: Relevance
“…Even within the same model – like in ZDF rats used in the present study – controversial data has been published. Some reported an increase in the number of apoptotic cells already in 19 week-old ZDF rats 48 while in another report on 23 week-old animals by Johnson and co-workers 25 and also in a previous work of our group on 32 week-old rats 56 no cell loss was observed. The reason behind this discrepancy is currently unknown but due to its huge potential impact on diagnosis and therapy it calls for further studies.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Even within the same model – like in ZDF rats used in the present study – controversial data has been published. Some reported an increase in the number of apoptotic cells already in 19 week-old ZDF rats 48 while in another report on 23 week-old animals by Johnson and co-workers 25 and also in a previous work of our group on 32 week-old rats 56 no cell loss was observed. The reason behind this discrepancy is currently unknown but due to its huge potential impact on diagnosis and therapy it calls for further studies.…”
Section: Discussionmentioning
confidence: 50%
“…Immunocytochemistry is probably the most sensitive and adequately selective method for identifying RGCs. Due to their diverse subtypes, all antibodies available to date label only a portion, some of them even the vast majority of the RGC population but never all RGCs 56 . There are also evident differences in sensitivity and labelling characteristics between the antibodies available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the foveal cones appear to be mostly affected revealing a loss of approximately 30% of the M-cones 7 weeks after type 2 diabetes was induced in the animals [46]. Studies in rats also have shown alterations in the photoreceptor outer segments with the S-cones and the M-cones most severely affected [47].…”
Section: Outcomes Of Irbp's Decreased Levels In Diabetesmentioning
confidence: 99%
“…Also, damage to the pigment epithelium was shown with a loss of ganglion cells. Other retinal cell types showed no evident alterations [12].…”
Section: Introductionmentioning
confidence: 98%